PENDIDIKAN KEBAHAGIAAN DI SEKOLAH;: Menyiapkan Generasi Indonesia Emas 2045 - wahyudi setiawan (Pendidikan Agama Islam, 2020)
Everyone's happiness has various causes. Everyone has different conditions of happiness. Human journey is always within the realm of achieving happiness during life. Schools become an important medium to teach everyone in the days of students to know and be able to achieve ways to be happy. Knowledge in this school will be a provision for every generation to get a happy and happy life. Through the literature review approach of each idea that discusses how to achieve happiness in education, this paper presents ideas for education in schools in order to prepare a golden generation of Indonesia. Indonesia has the potential to get a happy and advanced life of its people through increasing demographic bonuses and digital trends. Formal and non formal education institutions have important responsibilities to prepare happy and happy generations.